2013
DOI: 10.5194/gmd-6-457-2013
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of ash and SO<sub>2</sub> emissions from volcanic eruptions in WRF-Chem: development and some applications

Abstract: Abstract. We describe a new functionality within the Weather Research and Forecasting (WRF) model with coupled Chemistry (WRF-Chem) that allows simulating emission, transport, dispersion, transformation and sedimentation of pollutants released during volcanic activities. Emissions from both an explosive eruption case and a relatively calm degassing situation are considered using the most recent volcanic emission databases. A preprocessor tool provides emission fields and additional information needed to establ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 47 publications
0
56
0
Order By: Relevance
“…The new error covariance matrix Bnew represents the uncertainty of u b ,new that should be smaller than Bk. The vertical distribution could be based on explicit assumptions, such as uniform‐distributed [ Dacre et al , ], umbrella‐shaped [ Stuefer et al , ; Webley et al , ], Poisson‐distributed, exponentially distributed plume [ Searcy et al , ], or based on characteristics of the current eruption type.…”
Section: Assimilation Methodologymentioning
confidence: 99%
“…The new error covariance matrix Bnew represents the uncertainty of u b ,new that should be smaller than Bk. The vertical distribution could be based on explicit assumptions, such as uniform‐distributed [ Dacre et al , ], umbrella‐shaped [ Stuefer et al , ; Webley et al , ], Poisson‐distributed, exponentially distributed plume [ Searcy et al , ], or based on characteristics of the current eruption type.…”
Section: Assimilation Methodologymentioning
confidence: 99%
“…Resolving more meso-scale circulations, and improved representation of topography can be particularly advantageous, as they can cause large gradients in CO 2 (de Wekker et al, 2005;van der Molen and Dolman, 2007). While WRF-Chem is used for a variety of atmospheric transport studies (among others: Tie et al, 2009;de Foy et al, 2011;Lee et al, 2011;Stuefer et al, 2013), more general air quality studies have shown that an ensemble of models can forecast air pollution situations more accurately than a single model (Galmarini et al, 2004(Galmarini et al, , 2013. While in our research we focused on the transport of CO 2 and 14 CO 2 , other chemically active tracers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Different dust schemes will produce different dust emission fluxes over arid and semi-arid regions (Zhao et al, 2010;Su and Fung, 2015). Several factors, such as potential source regions, threshold friction velocity, size distribution, and other surface and soil-related parameters used in equations, can be the primary causes for the inconsistency, and the differences in simulated dust emissions will affect the characteristics of spatial-temporal variations of atmospheric aerosol particles.…”
Section: Dust Schemementioning
confidence: 99%